2017
DOI: 10.3171/2016.9.peds16283
|View full text |Cite
|
Sign up to set email alerts
|

International multicenter cohort study of pediatric brain arteriovenous malformations. Part 1: Predictors of hemorrhagic presentation

Abstract: OBJECTIVE Brain arteriovenous malformations (AVMs) are the most common cause of spontaneous intracranial hemorrhage in pediatric patients (age < 18 years). Since the cumulative lifetime risk of AVM hemorrhage is considerable in children, an improved understanding of the risk factors influencing hemorrhagic presentation may aid in the management of pediatric AVMs. The aims of this first of a 2-part multicenter, retrospective cohort study are to evaluate the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 71 publications
2
55
1
4
Order By: Relevance
“…In our literature review we report that 82% (95% CI = [77–87]; N  = 267) of children diagnosed with brain AVMs (mean age 11.4 ± 0.4) presented with rupture over the last 22 years included. In spite of a previous report of increased risk of haemorrhage associated with female sex [8], our review revealed a significant difference in gender-related AVM rupture (136 males vs 84 females) ( p  < 0.001). These findings perhaps propose that hormonal changes around puberty may be related, and suggest that the sex difference may be attributable to the hormonal differences too.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In our literature review we report that 82% (95% CI = [77–87]; N  = 267) of children diagnosed with brain AVMs (mean age 11.4 ± 0.4) presented with rupture over the last 22 years included. In spite of a previous report of increased risk of haemorrhage associated with female sex [8], our review revealed a significant difference in gender-related AVM rupture (136 males vs 84 females) ( p  < 0.001). These findings perhaps propose that hormonal changes around puberty may be related, and suggest that the sex difference may be attributable to the hormonal differences too.…”
Section: Discussioncontrasting
confidence: 99%
“…A high percentage of children with AVMs, often more than 60%, present with rupture [7, 8, 15, 17, 25]. In our series, 78.7% presented with haemorrhage.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations